“Work:” The Shift fr om Empathy to Sympathy in The York Play of the Crucifixion - Gutiérrez-Ortiz, María del Mar (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Abstract: The raising of the cross in the The York Play of the Crucifi xion shift s the empathic connection of the audience with the soldiers to a sympathetic bond with Christ. The mirror neuron system and theory of the mind have been used to defi ne and draw a distinction between the concepts of empathy and sympathy. Given that Bacon’s theory of perception provides a historical fr ame of reference for such emotional responses, this paper analyzes the language, the props and the staging of the play to explore the nature of the audience’s relationship with the characters. The conclusion reached is that the immediate impact of the raising of the cross has been largely disregarded: it is the end of the soldiers’ work that brings about the shift fr om empathy to sympathy. Work is not only the alienating force that enables the soldiers to carry out the crucifi xion with indiff erence, but also the main connection between the spectators, the characters and the actors. Keywords: empathy, sympathy, York, pageant, play, mystery cycle, crucifixion, audience, spectators, affective piety, compassion, work